Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1038/bjc.1990.240
|View full text |Cite
|
Sign up to set email alerts
|

Is apocrine differentiation in breast carcinoma of prognostic significance?

Abstract: Summary Apocrine differentiation in human breast cancers has been assessed using immunohistochemistry to detect zinc a2 glycoprotein and the findings related to standard prognostic factors, disease free interval (DFI) and survival in 145 women with early breast cancer. Breast tumour samples from women with a minimum follow-up of 5 years were assessed. Routinely fixed and processed tissue was used throughout. Sixty-six (45%) tumours did not stain with the antibody. Fifty-two (36%) exhibited positive apocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The importance of apocrine differentiation in breast carcinomas is uncertain because the incidence of apocrine change is difficult to establish, although extensive apocrine changes are reported in about 4% of invasive breast carcinomas. 41 Bundred et al 42 found that apocrine differentiation in breast carcinoma is associated with poor prognosis, although they could not explain the reasons for such, and suggested further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of apocrine differentiation in breast carcinomas is uncertain because the incidence of apocrine change is difficult to establish, although extensive apocrine changes are reported in about 4% of invasive breast carcinomas. 41 Bundred et al 42 found that apocrine differentiation in breast carcinoma is associated with poor prognosis, although they could not explain the reasons for such, and suggested further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have confirmed that ZAG is a reliable immunohistochemical marker of apocrine cell differentiation of mammary epithelial tissues (7,8,35,36,(52)(53)(54)(55)(56). Sanchez et al (28) have shown that many proteins are expressed in breast cancer cell line, and ZAG is one of them.…”
Section: Zag As a Biomarkermentioning
confidence: 98%
“…Apocrine carcinoma is a rare lesion that represents about 0.5% of all invasive breast carcinomas according to the Danish Breast Cancer Cooperative Group (DBCG) Registry, and even though these lesions are morphologically distinct from other breast carcinomas, there are at present no available standard histopathological criteria for their diagnosis [2][3][4] and as a result, there is no precise information as to their prognosis. Molecular profiling of breast cancer tumours with cDNA microarrays have provided a new way to classify breast tumours in subgroups based on their expression patterns [5], as well as to derive signatures for prognosis [6][7][8] and response to treatment [9][10][11].…”
Section: Introductionmentioning
confidence: 99%